The Crime of Sexual Intercourse Against Children Criminology and Victimology Perspective - I Made Wahyu Chandra Satriana; Ni Made Liana Dewi (IHSA Institute, 2021)
The crime of sexual intercourse is a type of crime related to a person's sexual activity with another person who is helpless, such as children or women. Within the jurisdiction of the Bali Police, the prevention of the crime of sexual intercourse with children is viewed from the criminological and victimological aspects. This research is an empirical legal research. The approach method used is the criminological approach, victimological approach, case approach, and fact approach. Using primary and secondary data obtained by means of interviews and document studies. Factors causing the occurrence of criminal acts of sexual intercourse with children are caused by internal and external factors. Internal factors are caused by mental weakness while external factors are caused by lack of attention from parents to children, economic factors, environment, technology, alcoholic beverages. Efforts to overcome the crime of sexual intercourse with children are carried out through preventive and repressive efforts.